Isolation and screening of yeast isolates indigenous palm wine for ethanol production - Antia, Ukponobong E.; Akan, Otobong D.; Eno-Ibanga, Cheryl K.; Akpan, Nseobong G. (2018)
The problem that has been ravaging ethanol producing industries for decades now is the ability of industrial yeast isolates to withstand ethanol production stress conditions while giving out optimal ethanol yeast. Hence, there is need to constantly source for yeast isolates with these qualities. Yeast isolates obtained from aging palm-wine were investigated for their ability to withstand some ethanol production stress conditions. Their growth responses were observed qualitatively at different temperatures, sugar concentrations (up to 200 g/L), and ethanol concentration (up to 20% v/v). A total of 20 yeast isolates were obtained and screened for ethanol stress condition tolerance. Saccharomyces cerevisiae SCPW 17 was able to tolerate ethanol production stress conditions with minimal growth at 45°C and 20% v/v ethanol and intensive growth in a medium containing 200 g glucose/L. The identity of S. cerevisiae SCPW 17 was determined and confirmed by the analysis of its internal transcribed spacer (ITS1) region of the 18S ribosomal DNA. Saccharomyces cerevisiae SCPW 17 exhibited good characteristics needed in yeast isolates meant for ethanol and bio-ethanol production.